The Coadministration of Unoxidized and Oxidized Desi Ghee Ameliorates the Toxic Effects of Thermally Oxidized Ghee in Rabbits - Alam Zeb; Islam Uddin (Journal of Nutrition and Metabolism)
Desi Ghee was thermally oxidized at 160°C for 9 h and characterized for peroxide value (PV), free fatty acid (FFA), thiobarbituric acid reactive substances (TBARS), radical scavenging activity (RSA), and fatty acid and cholesterol composition using GC-MS. Oxidized (OG) and normal ghee (NG) were fed to rabbits in different doses. Blood was collected for hematology and biochemical analyses after 7 and 14 days. The oxidation of desi ghee increased the PV, FFA, and TBARS values and showed a decline in the RSA values. GC-MS revealed that desi ghee was rich in saturated fatty acids (55.9 g/100 g) and significant amounts of oleic acid (26.2 g/100 g). The OG significantly decreased the body weight, which was normalized by the coadministration of NG. Serum lipid profile showed a dose dependent increase in total cholesterol, triglycerides, and low density lipoproteins (LDL) and decrease in RBCs count, hematocrit, glucose, and hemoglobin concentration with OG feeding. These parameters were normalized by coadministration of NG. Liver histopathology of OG fed groups showed bile duct dilation and necrotic changes, while normal architecture showed in NG groups, compared to control. These results indicate that NG has no significant effect on rabbits comparing with OG and that it was beneficial when coadministered with oxidized ghee.